The role communication, informativeness, and social presence play in the social media recruitment context of an emerging economy - Kai Si; Tariq Jalees; Syed Imran Zaman; Syed Hasnain Alam; Sherbaz Khan (Cogent Business & Management, 2023)
Both individuals and organizations extensively use the internet and social media for communications and other purposes in the present era. The study examines the impact of social media effectiveness on informativeness and communication. It also explores the effect of informativeness and communication on the recruitment process. The study also examined the mediating roles of informativeness and communication and the moderating role of social presence. The study has focused on the banking sector of Karachi, Pakistan. The study's enumerators distributed 450 questionnaires to the HR departments of the targeted banks and received 427 valid questionnaires. For data analysis, the study used Smart PLS version 3.2. It includes reliability, validity analyses, and generating a structural model for testing the hypotheses. The study's results support seven hypotheses and reject one hypothesis. The study found that social media positively affect informativeness, communication, and recruitment. The study also validated the (i) mediating role of informativeness on social media effectiveness and (ii) the mediating role of communication on social media effectiveness and recruitment process. The study also supported the positive moderating roles of social presence on informativeness and the recruitment process, but it failed to support that social presence positively moderates communication and the recruitment process.
Keywords: 650; communication and recruitment process; informativeness; social media presence; social-media effectiveness